2015
DOI: 10.1161/circgenetics.114.000597
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Endothelial Growth Factors

Abstract: Background Endothelial growth factors including angiopoietin-2 (Ang-2), its soluble receptor Tie-2 (sTie-2) and hepatocyte growth factor (HGF) play important roles in angiogenesis, vascular remodeling, local tumor growth and metastatic potential of various cancers. Circulating levels of these biomarkers have a heritable component (between 13% and 56%), but the underlying genetic variation influencing these biomarker levels is largely unknown. Methods and Results We performed a genome-wide association study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…In a literature search, we identified suitable IVs for IL-1ra (rs4251961 and rs6759676) ( 15 ), HGF (rs5745687) ( 16 ), and t -PA (rs9399599, rs3136739, and rs7301826) ( 17 ). In a GWAS for the remaining four biomarkers using the conventional threshold for genome-wide significance ( P < 5 × 10 −8 ), we found a suitable genetic IV for cathepsin D only (rs55861089) ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a literature search, we identified suitable IVs for IL-1ra (rs4251961 and rs6759676) ( 15 ), HGF (rs5745687) ( 16 ), and t -PA (rs9399599, rs3136739, and rs7301826) ( 17 ). In a GWAS for the remaining four biomarkers using the conventional threshold for genome-wide significance ( P < 5 × 10 −8 ), we found a suitable genetic IV for cathepsin D only (rs55861089) ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[100][101][102][103][104] With regard to ARDS, ABO variation that determines blood type is strongly associated with plasma levels of multiple endothelial-derived glycoproteins important in ARDS, including VWF, intercellular adhesion molecule 1 (ICAM-1), and Ang-2. [104][105][106][107][108] It is possible that a therapeutic targeting these proteins or the endothelium in general could have a distinct effect in different blood types, a genetic trait that is easily accessible clinically.…”
Section: Genetic and Biomarker-defined Endotypes Of Ardsmentioning
confidence: 99%
“…We have shown that rs2920656 is an intronic variant in MCPH1 that regulates plasma ANG-2 concentrations. Previous studies have identified genetic variants in MCPH1 [ 37 ] and ANGPT2 [ 38 ] that are associated with ANG-2 concentrations. It is also conceivable that rs2920656 influences MCPH1 expression.…”
Section: Discussionmentioning
confidence: 99%